Revisión de los contratos colectivos en relación al mandato 08 referente a la intangibilidad de los derechos del trabajador. - Freire Amaya, Mayra Alejandra (2015)
The progress of societies throughout history has always based on the work, which was initially carried out with abuse to the worker; in the majority of occasions was caused by mean governors and patrons, with that unbearable situation that workers used to live with, it made them to look for force in the union which they lacked in an individual way. The first workers associations appeared which became in a collective association and negotiation right perfecting the collective contract, recognized by the International Workers Organization, besides the principles such as indispensability and intangibility of the workers’ rights. However, with all these implementations for the benefit of the working class in the current times the workers’ rights are still being violated, that is why the need to carry out an investigative study in which it could be possible to determine which those rights and principles are violated The first chapter of the present investigative work shows the rights, principles and agreements that characterize the boss-employee relations, having as base the Constitution of the Republic of Ecuador and Agreements and International Instruments Human Rights. The second chapter shows the interpretations and analysis of each one of the questions that made up the surveys done to the people related to the working aspect and the current problem In the third chapter, the established proposal was carried out having as a base the obtained information, establishing in this way, the solution to the problem to the xi violation to a series of rights and principles that legally have been acquired and recognized by the workers, which have not been respected because of the creation of norms that do not keep obedience and subordination to constitutional and international order.